2022
DOI: 10.3389/fpubh.2022.953545
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unhealthy dietary habits on the incidence of dental caries and overweight/obesity among Egyptian school children (A cross-sectional study)

Abstract: BackgroundObesity and dental caries are public health problems in Egypt. Factors such as unhealthy diet, poor oral hygiene, and physical inactivity can play a major role in both problems. This study was carried out to illuminate the mutual unhealthy dietary risk factors associated with the incidence of both health conditions.MethodsBetween 1 October 2020 and 1 July 2021, 369 Egyptian children (5–10 years) were examined. Dental status was assessed using decayed, missing/extracted, and filled tooth indices (dmft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 93 publications
1
12
0
Order By: Relevance
“…Micronutrient deficiency has also been linked with periodontitis. [ 29 30 31 ] However, with the rise in multiple facets of the nutrition problems, and more specifically relating to obesity and dental problems, the recommendations and education, needs to be started early during school days. Studies have shown a positive association between obesity and primary dentition caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronutrient deficiency has also been linked with periodontitis. [ 29 30 31 ] However, with the rise in multiple facets of the nutrition problems, and more specifically relating to obesity and dental problems, the recommendations and education, needs to be started early during school days. Studies have shown a positive association between obesity and primary dentition caries.…”
Section: Discussionmentioning
confidence: 99%
“…It’s no more how much you can take; rather, it depends more on how better it can be digested and how promptly we can choose the best dietary options. [ 29 32 , 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in Canadian preschoolers that utilized FFQs submitted by children’s parents indicated that flavored milk was a leading contributor of free sugars to the children’s diets; it contributed 3.1% of total energy [ 36 ], which fell within recommendations from the WHO [ 35 ]. Another cross-sectional analysis conducted in Egyptian children ages 5–10 y that aimed to assess relationships between dietary habits, overweight and obesity, and dental carries, also by utilizing FFQs submitted by children’s parents, indicated an association between sweetened milk consumption and dental carries [ 37 ]. Unfortunately, the statistical analysis did not include adjustments for lifestyle factors, only for age and gender, making it difficult to determine the strength of the observed relationship.…”
Section: The Role Of Flavored Milk In Risk Of Dental Carries Among Ch...mentioning
confidence: 99%
“…This diverse ecosystem of oral microbiota plays a crucial role through functional pathways in maintaining oral health, preventing dental diseases, promoting proper digestion and nutrient absorption [ 3 ]. Although, factors such as poor oral hygiene practice, unhealthy diet and genetic disorders can result to development of oral disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%